2016
DOI: 10.1038/ncomms13134
|View full text |Cite
|
Sign up to set email alerts
|

The solution structure of an anti-CRISPR protein

Abstract: Bacterial CRISPR–Cas adaptive immune systems use small guide RNAs to protect against phage infection and invasion by foreign genetic elements. We previously demonstrated that a group of Pseudomonas aeruginosa phages encode anti-CRISPR proteins that inactivate the type I-F and I-E CRISPR–Cas systems using distinct mechanisms. Here, we present the three-dimensional structure of an anti-CRISPR protein and map a functional surface that is critical for its potent inhibitory activity. The interaction of the anti-CRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 12 publications
2
43
1
Order By: Relevance
“…AcrF1 also directly interacts with residues that appear to be important for DNA-binding. The structure of AcrF1 determined by cryoEM matched a previously solved NMR structure [28], and key functional residues identified through mutagenesis in this study interact closely with residues in Cas7f. AcrF2 was shown to bind a portion of Cas8f involved in DNA-binding activity [27].…”
Section: Anti-crispr Mechanismssupporting
confidence: 68%
“…AcrF1 also directly interacts with residues that appear to be important for DNA-binding. The structure of AcrF1 determined by cryoEM matched a previously solved NMR structure [28], and key functional residues identified through mutagenesis in this study interact closely with residues in Cas7f. AcrF2 was shown to bind a portion of Cas8f involved in DNA-binding activity [27].…”
Section: Anti-crispr Mechanismssupporting
confidence: 68%
“…Since high-resolution structural information available on AcrF1 at present is from NMR studies (Maxwell et al, 2016), we also determined the crystal structure of AcrF1 to test for any differences. As shown in Figure S6C, AcrF1 is composed of a three-stranded β-sheet with two α-helices positioned along one face of the β-sheet, and there are minimal differences between the NMR and crystal structures.…”
Section: Resultsmentioning
confidence: 99%
“…However, a high-resolution crystal structure of the P. aeruginosa Cas6 protein bound to the 3′ stem-loop of the crRNA was previously determined (Haurwitz et al, 2010) and the EM density in this region was sufficiently resolved to enable unambiguous rigid body fitting of the atomic model into position at the head of the complex (Figure 1). In addition, two copies of an NMR structure for AcrF1 were used to facilitate model building (Maxwell et al, 2016). Models for AcrF2 and all other Cas proteins were built de novo using the EM density.…”
Section: Structural Overview Of the Csy Complexmentioning
confidence: 99%
“…AcrF1 is a small protein (78 residues) composed of a four-stranded antiparallel β-sheet, flanked on one side by two α-helices (β 1 β 2 β 3 β 4 α 1 α 2 ) (Figure 1D and 2). The AcrF1 structure was previously determined by NMR, and mutational studies identified three residues (Y6, Y20, and E31) on one face of the β-sheet that are critical for AcrF1-mediated repression of type I-F immune response (Maxwell et al, 2016). Here we show that these three residues interact with a single, conserved lysine (K85) on the Cas7f thumb, and that a lysine to alanine mutation at this position (K85A) results in a faster dissociation rate from the complex (k d1 =3.1x10^-4/sec) as compared to the dissociation rate of AcrF1 from the wild type Csy complex (k d1 =2.1x10^-7/sec) (Figures 4D, S7, S8, and S9).…”
Section: Acrf1 Proteins Prevent Dna Hybridizationmentioning
confidence: 99%